Lung transplant graft salvage using aortic homograft for bronchial dehiscence. (5th September 2020) - Ram, Duvuru; Mathew, Geevarghese; Lewis, Christopher; McWilliams, Tanya; O'Carroll, Mark; Lund, Jens Teglgaard; Sibal, Amul Kumar
Abstract: The use of aortic homograft in infective pathology is well described. Its use in the repair of post-transplant airway complications has been seldom reported. Herein, we report our experience with the successful use of aortic homograft in the management of post-transplant large airway complications in two patients. Abstract : Major airway complications (ACs) following lung transplantation are uncommon but contribute to significant morbidity and mortality [1].